Scale up for Linux on LinuxONE - Simoes Franco, Eduardo; Cardeneti Mendes, Felipe (IBM redpaper., 2019)
This book was written by IBM® IT specialists who have experience implementing Linux solutions on IBM LinuxONE™ (LinuxONE). The contents of this book follow the guidelines from Linux regarding LinuxONE installations. The preferred practices that are described in this book are gathered from the experiences of those specialists in hundreds of projects at IBM and customer environments. This IBM Redbooks® publication provides you with the information needed in making a decision on scaling architecture when implementing Linux on LinuxONE. This book has the following goals: To inform you about x86 sprawl problems To inform you that x86 Vertical Scale out architectures are problematic going forward To provide solutions to x86 server sprawl problems To inform you about the LinuxONE solution for each x86 server sprawl problem To provide virtulization and security options for LinuxOne The scaling up and scaling out architectures enable you to scale the capacity of an existing system to accommodate sporadic application demands or application workloads. This provides some freedom to operate in the environment. However, if this activity is performed without correct planning and the correct architecture choice, it leads to server sprawl where your environment houses more servers than it should based on its current and predicted requirements. This can potentially cause your enterprise to both waste resources and increase costs. Although scaling out on x86 systems is a common form of growth because of inexpensive x86 systems, the scale out can easily become a problem in terms of total cost of ownership (TCO) when the environment starts to increase the number of physical servers and the resources needed to maintain them. LinuxONE servers solve the sprawl problem caused by the scaling out of x86 servers, and are an excellent choice for cloud, mobile, big data, blockchain, analytics, and other workloads that require a robust and flexible environment. This publication describes the advantages and disadvantages of the LinuxONE scaling option. The audience for this publication consists of the following groups: Customers, IBM Business Partners, IT architects and IT Specialists planning and installing Linux on LinuxONE System administrators managing the Linux Systems.